2016
DOI: 10.1095/biolreprod.116.142075
|View full text |Cite
|
Sign up to set email alerts
|

Embryo Mortality Around the Period of Maintenance of the Corpus Luteum Causes Alterations to the Ovarian Function of Lactating Dairy Cows

Abstract: Objectives were to identify cows with embryo mortality (EM) around the period of corpus luteum maintenance by interferon tau (IFNT) and to characterize ovarian function in cows that underwent EM. Lactating Holstein cows received artificial insemination (AI) (Day = 0) with semen or extender only. From Day 14 to 42 transrectal ultrasonography was performed daily to monitor ovarian dynamics and uterine contents whereas blood was collected every 48 h to determine ISG15 and MX2 mRNA abundance in blood mononuclear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…A much larger study evaluating the time between successive inseminations in the same cow in the same lactation, the inter-service interval (ISI), suggests that ISIs in excess of the normal range are frequent, with 22 days being the modal interval and that the traditional normal range of 18 to 24 days may poorly reflect the observed distribution of intervals in the population [6], a similar pattern has been identified in progesterone profiles [7]. Some of these longer ISIs could be the result of late embryonic death [8][9][10], this may impact on their chance of conception at the next insemination. It is not clear whether cows inseminated at these apparently abnormal intervals are as likely to conceive as those inseminated within the traditional expected range.…”
Section: Introductionmentioning
confidence: 94%
“…A much larger study evaluating the time between successive inseminations in the same cow in the same lactation, the inter-service interval (ISI), suggests that ISIs in excess of the normal range are frequent, with 22 days being the modal interval and that the traditional normal range of 18 to 24 days may poorly reflect the observed distribution of intervals in the population [6], a similar pattern has been identified in progesterone profiles [7]. Some of these longer ISIs could be the result of late embryonic death [8][9][10], this may impact on their chance of conception at the next insemination. It is not clear whether cows inseminated at these apparently abnormal intervals are as likely to conceive as those inseminated within the traditional expected range.…”
Section: Introductionmentioning
confidence: 94%
“…In addition to its use for pregnancy detection, measurement of ISG expression has also been used for evaluating embryo survival/mortality (Han et al 2006, Wijma et al 2016.…”
Section: Interferon-stimulated Genes and Pregnancy Diagnosismentioning
confidence: 99%
“…Based on plasma PAG levels, more than half of the cows in cluster 5 maintained their original CL because they became pregnant and then underwent early pregnancy loss. In addition, it is likely that some or most cows in cluster 5 without detectable PAG levels 25 or 32 d after TAI could have undergone early pregnancy loss shortly after maternal recognition of pregnancy (Wijma et al, 2016), resulting in enough time to clear residual PAG from circulation before 25 to 32 d after TAI. Nonetheless, not all cows in cluster 5 had detectable PAG levels at 25 or 32 d after TAI in the present experiment.…”
Section: Pag 25 and 32 D After Taimentioning
confidence: 99%
“…Similarly, Santos et al (2004) reported a 34% pregnancy loss rate between 2 and 8 d after AI and a 20% pregnancy loss rate between 6 and 28 d after AI compared with a 12.5% pregnancy loss rate between 28 and 42 d, an 8.5% pregnancy loss rate between 42 and 90 d, and a 6% pregnancy loss rate from 90 d until calving. Cows undergoing early pregnancy loss have extended luteal phases (>27 d; Wijma et al, 2016). In addition, cows undergoing late embryonic loss have increased interferon-τ stimulated genes 18 to 22 d after AI and increased PSPB concentrations in circulation beginning 24 d after AI, whereas cows undergoing early pregnancy loss have increased interferon-τ stimulated genes 18 to 22 d after AI but may not have increased PSPB concentrations (Wijma et al, 2016).…”
Section: Pag 25 and 32 D After Taimentioning
confidence: 99%
See 1 more Smart Citation